Analisis Perilaku Kolusif pada Tender Perbaikan Jalan di Provinsi DKI Jakarta Tahun 2011-2014 - Darmawan, Sastyo Aji; Khoirunurrofik, Khoirunurrofik (UI Scholars Hub, 2015)
One of the great progress that has been achieved by the Government in the procurement of goods/services or tender is the implementation of the procurement of goods/services through an electronic system (e-procurement). Although the implementation of e-procurement is believed to increase transparency and accountability, however in practice the unfair competition tenders are still found. Meanwhile, to enforce the Competition Law, KPPU uses indirect evidence that can be either an economic analysis or the evidence of communication for deciding collusion in tenders. This study aimed to analyze firm behavior in tender by testing a method that refers to the rules of a competitive tender offer, which are conditional independence and exchangeability test. Focusing on Jakarta’s road repairs tender, this study identifies that there are seven firms that suspected of doing a collusion in the tender as they are failed to pass both of tests.